Natural transform of fractional order and some properties - Omran, Maryam; Kilicman, Adem (Cogent OA, 2016)
In this work, a new fractional integral transform is proposed, and some of its properties are mentioned. Further, the relation between it and others fractional transforms is given and some of its applications are presented.